A hybrid attention-based deep learning framework for high-accuracy microplastic detection and monitoring in water environments - Xinyu Zhang; Cheng-Hao Yu; Rong Fu; Leixin Ouyang; Ziliang Zhang; Lina Pu; Mark Ming-Cheng Cheng (Water Research, 2027)

An experimental study on the effects of soft biofouling on the hydrodynamic characteristics of the net cage - Ming-Shan Sun; Chun-Wei Bi; Yuan-Mao Zhang; Rong-Ping Liu; Liu-Yi Huang (Biosystems Engineering, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Immunotherapy in multiple myeloma: advances from immune microenvironment insights to clinical application - Yao Zhang; Yuting Lei; Yanzhao Huang; Yan Gao; Rong Liu; Kaiyun Guo; Chunlian Zhao; Ming Lei (Molecular Biology Reports, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Functional identification of the gene encoding enoyl-CoA hydratase for siderophore biosynthesis in the entomopathogen Beauveria bassiana - Ting-Fei Sun; Hao Zhang; Hang-Rong Xu; Ben-Jie Gao; Ming-Guang Feng; Sheng-Hua Ying (Fungal Biology, 2026)

Regulating proton back-diffusion to enhance lithium sulfate conversion in bipolar membrane electrodialysis - Rong Zhang; Lingyun Wang; Xin Wang; Zhe Yu; Wenkai Wang; Ming Tan; Yang Liu; Yang Zhang (Desalination, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Impact of heat-moisture treatment on cooking characteristics, structural features, and low digestion of japonica rice - Rong Zhou; Jingyi Zheng; Zhengyu Jin; Tao Zhang; Ming Miao (Food Bioscience, 2026)

Rapid in-situ recovery of starved anammox consortia: Metabolic stimulation and microbial synergy driven by organics and oxygen - Yihao Qiu; Chenrong Gu; Jiaqi Han; Jiaqi Zhang; Qi Zhang; Rong Li; Xiao-Ming Ji (Environmental Research, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

Callosobruchus maculatus feeding triggers multilevel defenses in cowpea seeds: from germination regulation to defensive metabolite biosynthesis - Hainuo Hong; Ming Zhang; Jiamei Geng; Qiulin Chen; Zheyi Shi; Yang Gao; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Extracellular polymeric substances: overlooked contributors to soil organic carbon persistence - Yichao Wu; Yuwei Yi; Minsu Kim; Samuel Bickel; Ming Zhang; Ke Dai; Chunhui Gao; Chenchen Qu; Chuisi Kong; Mengxi Feng; Ke-Qing Xiao; Hans-Curt Flemming; et al. (Soil Biology and Biochemistry, 2026)

Retraction notice to “Grassland greening impacts on global land surface temperature” [Sci. Total Environ. 838 (2022) 155851] - Xiangjin Shen; Yiwen Liu; Liyuan Wu; Rong Ma; Yanji Wang; Jiaqi Zhang; Lei Wang; Binhui Liu; Xianguo Lu; Ming Jiang (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Debris flow vulnerability assessment in the Eastern Tibetan Plateau using integrated UAV-SLAM 3D reconstruction: Shuihaizigou Gully case study - Haoyu Li; Jianqiang Zhang; Yunyuan Li; Lili Zhang; Zaiyang Ming; Rong Chen (Landslides, 2026)

Multifaceted transcriptional regulation of siderophore biosynthesis by the bZIP transcription factor HapX in the entomopathogenic fungus Beauveria bassiana under the iron-deficiency conditions - Ting-Fei Sun; Hao Zhang; Hang-Rong Xu; Ben-Jie Gao; Ming-Guang Feng; Sheng-Hua Ying (Pesticide Biochemistry and Physiology, 2026)

Host switching and successive subculturing drive adaptive responses in Liriomyza sativae - Yang Gao; Wei He; Ming Zhang; Hai-Nuo Hong; Jin Wang; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Eliminating high-voltage phase transitions and oxygen loss in O3-type sodium layered cathodes via reversible solid-solution and anionic-redox chemistry - Lin-Rong Wu; Yu-Han Zhang; Zhen Wu; Hui Wu; Nian Zhang; Ding Zhang; Xiaochuan Duan; Xian-Ming Zhang (Science Bulletin, 2026)

Corrigendum to “Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China” [Sci. Total. Environ., Volume 874 (2023), 162397] - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Ruichang Shen (Science of The Total Environment, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Anode interface layers constructed in situ by multifunctional carbon dots for ultra-stable aqueous zinc-ion batteries - Qian-Li Ma; Xi-Rong Zhang; Bao-Juan Wang; Hao-Wen Sun; Huan-Ming Xiong (Chemical Engineering Journal, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Characteristics of VOCs emissions and environmental impact assessment of typical automobile manufacturing enterprises in Beijing, China - Yinquan Qiu; Xinyu Zhang; Rong Sun; Houjian Yang; Ming Liu; Lianhai Ren; Pan Wang (Air Quality, Atmosphere & Health, 2026)

Fine-tuning Atmospheric Parameters for Improving ENSO Simulation in the Zebiak–Cane Model - Xiaojun Wei; Lin Chen; Ming Sun; Ruihuang Xie; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Cover cropping shifts microbial life-history strategies to promote necromass carbon accumulation through soil metabolite mediation in orchard systems - Yutao Zhang; Jia Liu; Kailou Liu; Daming Li; Rong Cui; Yaxin Liu; Xingjia Xiang; Ming Liu (Soil and Tillage Research, 2025)

Structural characterizations and potential delivery platform of glucan dendrimer-derived hydrogel - Jingyi Zheng; Rong Zhou; Zhengyu Jin; Tao Zhang; Ming Miao (Carbohydrate Polymers, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Daily temperature fluctuations intensify the toxicokinetics and toxicodynamics of phenanthrene in Enchytraeus albidus (Oligochaeta), increasing overall toxicity risk - Naichuan Xiao; Ming Gao; Dong Zhu; Zifang Wang; Rong Huang; Lelin You; Tingting Zhang; Wencai Dai (Journal of Hazardous Materials, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Insights into mixotrophic metabolisms of anammox core consortia for rapid biofilm formation under low-oxygen conditions - Jiaqi Zhang; Hao Zhang; Ziyu Xu; Dayong Zhang; Guohao Yang; Quan Zhang; Rong Li; Xiao-Ming Ji (Chemical Engineering Journal, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Enrofloxacin drives the ultra-selective enrichment of Ca. Kuenenia stuttgartiensis under microaerobic conditions - Jiaqi Zhang; Hao Zhang; Zhenyi Ma; Lin Zhou; Qi Zhang; Quan Zhang; Chuan Chen; Rong Li; Xiao-Ming Ji (Journal of Hazardous Materials, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Enhancement of Ca2+ Signal Strength in Astrocytes in the Lateral Septum Improves Cognitive Disorders in Mice After Hemorrhagic Shock and Resuscitation - Wen-Guang Li; Lan-Xin Li; Rong-Xin Song; Xu-Peng Wang; Shi-Yan Jia; Xiao-Yi Ma; Jing-Yu Zhang; Gang-Feng Yin; Xiao-Ming Li; Li-Min Zhang (Neuroscience Bulletin, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Cessation of manure application diminishes the dissemination potential of antibiotic resistance genes by altering bacterial interaction patterns in soil–lettuce systems - Ruochen Li; Xin Pei; Ming Zhang; Xuhui Deng; Chengyuan Tao; Jiabao Wang; Xueli Chen; Nicholas Clarke; Lidia Sas-Paszt; Zongzhuan Shen; Rong Li; Qirong Shen (Applied Soil Ecology, 2025)

Manipulating molecular conformation of charge-transfer cocrystal for NIR-II absorption and light/thermal-responsive imaging - Yun Rong; Si-Qi Chen; Yu Dong Zhao; Sheng Zhuo; Yuan-Yuan Li; Jin-Zhuo Liu; Yi-Yi Ju; Yue-Min Xie; Liang-Sheng Liao; Ming-Peng Zhuo; Ke-Qin Zhang (Chemical Engineering Journal, 2025)

Addressing accuracy challenges in machine learning for debris flow susceptibility: Insights from the Yalong River basin - Zaiyang Ming; Jianqiang Zhang; Haiqing He; Lili Zhang; Rong Chen; Yang Jia (Journal of Mountain Science, 2025)

Divergent effects of biomass-derived carbon dots application and sweetpotato planting on accumulations of soil microbial necromass carbon in Vertisol - Jing Wang; Meng Zhu; Xiaoya Zhu; Qiangqiang Zhang; Yongchao Yu; Peng Zhao; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2025)

Nanomedicine constructed with plant-derived aromatic aldehydes treats low back pain by reversing the progression of lumbar facet joint osteoarthritis - Ming Yang; Hui Lv; Zhenzhen Tang; Jiangling Zhou; Qiandong Yang; Juan Cai; Yingtao Gui; Bo Yu; Rong Huang; Jing Yang; Ying Bao; Dinglin Zhang; et al. (Chemical Engineering Journal, 2025)

Genomic analysis of Vibrio sp. D3 reveals its role in marine sulfur cycling - Fei-Fei Li; Zhen-Kun Li; Ming-Chen Wang; Jia-Rong Liu; Na Wang; Zhi-Qing Wang; Yu-Zhong Zhang; Hui-Hui Fu (Marine Genomics, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Comparative analysis of three extraction methods for ginger leaf polysaccharide: Chemical composition, antioxidant activity, and hypolipidemic effects - Zhong-hao Zhang; Zhong-hua Zhao; Tian-yi Cao; Cai-rong Yang; Zi-zhong Tang; Shi-ling Feng; Shu Yuan; Sheng-lin Hu; Ming Yuan (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Overexpressing IbHAK5 increases drought stress tolerance in transgenic sweetpotato - Rong Jin; Peng Zhao; Qiangqiang Zhang; Ming Liu; Xiaoya Zhu; Jing Wang; Yongchao Yu; Zhonghou Tang (Plant Biotechnology Reports, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Foliar-Applied Carbon Dots Confer Enhanced Low Phosphorus Tolerance in Sweetpotato Seedling - Xiaoya Zhu; Jing Wang; Peng Zhao; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2025)

Utilization of dewatered alum sludge from water treatment plants as a sustainable green roof substrate - Yanyan Chi; Siyang Liu; Di Ming; Xiaoyu Huang; Rong Zhang; Keke Yin (Process Safety and Environmental Protection, 2025)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Long-term stationary fertilization decreased soil health in field-grown sweetpotato by increasing soil-borne diseases or allelochemicals - Xiaoya Zhu; Peng Zhao; Jing Wang; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Mining of novel target genes through Pan-genome analysis for Conventional PCR and Real-Time PCR detection of Staphylococcus argenteus in food - Jiahui Huang; Jingsha Dai; Ming Liu; Shixuan Huang; Yuwei Wu; Dongli Rong; Yuanyu Li; Miao Zhao; Ying Li; Jumei Zhang; Shi Wu; Qingping Wu (Food Control, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Versatile room temperature phosphorescence polymer with luminophore content as low as 0.05 wt% - Wen Wen Deng; Ze Ping Zhang; Min Zhi Rong; Ming Qiu Zhang (Chemical Engineering Journal, 2024)

Soil Organic Matter and Amorphous Oxides Determine the Surface Electrochemical Properties of Purple Soil Under Long-Term Inorganic and Organic Fertilization - Jun Xie; Rong Huang; Dongxun Wu; Wencai Dai; Zhengxin Deng; Yue Li; Xiaojun Shi; Yueqiang Zhang; Zifang Wang; Ming Gao (Journal of Soil Science and Plant Nutrition, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

In-situ electric swing adsorption enabling superior water vapor capture of salt-based carbon fibers - Rong Zhu; Yaowei Huang; Qiongfen Yu; Ming Li; Yunfeng Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Pleurotus eryngii root waste and soybean meal co-fermented protein improved the growth, immunity, liver and intestinal health of largemouth bass (Micropterus salmoides) - Jian-Ming Xu; Wen-Rong Gao; Ping Liang; Guo-He Cai; Hong-Ling Yang; Jian-Bin Lin; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

High-throughput analytical methodology of monoalkyl phthalate esters and the composite risk assessment with their parent phthalate esters in aquatic organisms and seawater - Qiang-Qiang Shi; Feng Xu; Tao Shen; Rong-Rong Zhang; Hua Liu; Ming-Ze Chen; Ai-Li Sun; Ze-Ming Zhang; Xi-Zhi Shi (Journal of Hazardous Materials, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Colloid-like tools fast beat viral bio-colloids: Micron-surface enrichment and in-situ inactivation induced by interface-decorated microbubbles - Ming Zhang; Kun Ye; Hongan Tao; Rong Cheng; Daoyong Zhang; Xiangliang Pan (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Impacts of climate change on fractional vegetation coverage of temperate grasslands in China from 1982 to 2015 - Rong Ma; Jiaqi Zhang; Xiangjin Shen; Binhui Liu; Xianguo Lu; Ming Jiang (Journal of Environmental Management, 2024)

TBK1 upregulates the interferon response against virus by the TBK1-IRF3/7 axis in yellow catfish (Pelteobagrus fulvidraco) - Li-ming Xiong; Lei Zhang; Zhe Long; Xiang Zhao; Yan-rong Ying; Tiao-yi Xiao; Shu-ting Xiong (Fish & Shellfish Immunology, 2024)

Iron isotope evidence in continental intraplate basalts for mantle lithosphere imprint on heterogenous asthenospheric melts - Rong Xu; Sarah Lambart; Oliver Nebel; Ming Li; Zhongjie Bai; Junbo Zhang; Ganglan Zhang; Jianfeng Gao; Hong Zhong; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Non-steroidal anti-inflammatory drugs (NSAIDs) in the environment: Recent updates on the occurrence, fate, hazards and removal technologies - Jia-yuan Lin; Yuan Zhang; Yu Bian; Yi-xin Zhang; Rong-zhu Du; Ming Li; Yue Tan; Xue-song Feng (Science of The Total Environment, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Towards disentangling the classification of freshwater fish trypanosomes - Peng Zhang; Jie Liu; Xiao-Ming Yin; Jun-Yu Zhou; Julius Lukeš; Zhao-Rong Lun; De-Hua Lai (Marine Life Science & Technology, 2023)
Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi . Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species.

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Experimental study on visualization of TBAB hydrate formation in confined small channels - Qi-Rong Zuo; Ming Gao; Peng Kong; Li-Xin Zhang (Fuel, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Zn anode surface engineering for stable zinc-ion batteries: Carbon dots incorporated mesoporous TiO2 as a coating layer - Tian-Bing Song; Qian-Li Ma; Xi-Rong Zhang; Jia-Wen Ni; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Effects of Long-term Non-application of Phosphorus Fertilizer on Bacterial Community Structure and Metabolite Profiles of Sweetpotato Rhizosphere - Xiaoya Zhu; Jing Wang; Qiangqiang Zhang; Peng Zhao; Ming Liu; Rong Jin; Yongchao Yu; Aijun Zhang; Zhonghou Tang (Journal of Soil Science and Plant Nutrition, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

HSPA12A was identified as a key driver in colorectal cancer GWAS loci 10q26.12 and modulated by an enhancer–promoter interaction - Zequn Lu; Linyun Fan; Fuwei Zhang; Chaoqun Huang; Yimin Cai; Can Chen; Gaoyuan Li; Ming Zhang; Jinyu Huang; Caibo Ning; Yanmin Li; Wenzhuo Wang; et al. (Archives of Toxicology, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Screening of pesticides in serum, urine and cerebrospinal fluid collected from an urban population in China - Ke-Xin Zhao; Ming-Yan Zhang; Dan Yang; Rong-Shu Zhu; Zi-Feng Zhang; Ying-Hua Hu; Kurunthachalam Kannan (Journal of Hazardous Materials, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Mineral residue accelerant-enhanced anaerobic digestion of cow manure: An evaluation system of comprehensive performance - Sining Yun; Tian Xing; Yi Wang; Rong Chen; Feng Han; Chen Zhang; Ming Zou (Science of The Total Environment, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Brain 5-HT2A receptor binding and its neural network related to behavioral inhibition system - Kazuho Kojima; Shigeki Hirano; Yasuyuki Kimura; Chie Seki; Yoko Ikoma; Keisuke Takahata; Takehito Ito; Keita Yokokawa; Hiroki Hashimoto; Kazunori Kawamura; Ming-Rong Zhang; Hiroshi Ito; et al. (Brain Imaging and Behavior, 2022)
The tendency to avoid punishment, called behavioral inhibition system, is an essential aspect of motivational behavior. Behavioral inhibition system is related to negative affect, such as anxiety, depression and pain, but its neural basis has not yet been clarified. To clarify the association between individual variations in behavioral inhibition system and brain 5-HT 2A receptor availability and specify which brain networks were involved in healthy male subjects, using [ 18 F]altanserin positron emission tomography and resting-state functional magnetic resonance imaging. Behavioral inhibition system score negatively correlated with 5-HT 2A receptor availability in anterior cingulate cortex. A statistical model indicated that the behavioral inhibition system score was associated with 5-HT 2A receptor availability, which was mediated by the functional connectivity between anterior cingulate cortex and left middle frontal gyrus, both of which involved in the cognitive control of negative information processing. Individuals with high behavioral inhibition system displays low 5-HT 2A receptor availability in anterior cingulate cortex and this cognitive control network links with prefrontal-cingulate integrity. These findings have implications for underlying the serotonergic basis of physiologies in aversion.

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Study on the impact of comprehensive urbanization on urban civil building CO2 emissions in China - Rong Guo; Nan Li; Hailin Mu; Ming Zhang; Xiyue Yang; Yixuan Han; Rongkang Yao; Zhihao Shao (Environmental Science and Pollution Research, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Upregulation of Striatal Metabotropic Glutamate Receptor Subtype 1 (mGluR1) in Rats with Excessive Glutamate Release Induced by N-Acetylcysteine - Tomoteru Yamasaki; Maki Okada; Atsuto Hiraishi; Wakana Mori; Yiding Zhang; Masayuki Fujinaga; Hidekatsu Wakizaka; Yusuke Kurihara; Nobuki Nengaki; Ming-Rong Zhang (Neurotoxicity Research, 2022)

Transgelin-2 interacts with CD44 to regulate Notch1 signaling pathway and participates in colorectal cancer proliferation and migration - Rong Ding; Guoyu Li; Yueyi Yao; Lijuan Zhang; Xuan Zhang; Jiayi Li; Tao Shen; Yi Gao; Tao Wu; Shuzhen Kong; Ming Huang; Yunfeng Li (Journal of Physiology and Biochemistry, 2022)

Overexpression of IbMPK3 increases low-temperature tolerance in transgenic sweetpotato - Rong Jin; Ho Soo Kim; Tao Yu; Ming Liu; Wenhui Yu; Peng Zhao; Aijun Zhang; Qiangqiang Zhang; Yaju Liu; Qinghe Cao; Sang-Soo Kwak; Zhonghou Tang (Plant Biotechnology Reports, 2022)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Soil bio-cementation using an improved 2-step injection method - Ming-Juan Cui; Jun-Jie Zheng; Rong-Jun Zhang; Han-Jiang Lai (Arabian Journal of Geosciences, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Analysis of nicotine-induced metabolic changes in Blakeslea trispora by GC-MS - Yang Liu; You-ran Shao; Xiang-yu Li; Zhi-ming Wang; Li-rong Yang; Yu-zhou Zhang; Mian-bin Wu; Jian-ming Yao (Journal of Zhejiang University-SCIENCE B, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Molecular cloning and characterization of genes related to the ethylene signal transduction pathway in pomegranate (Punica granatum L.) under different temperature treatments - Rong Huang; Wei Li; Xiao-Wan Guan; Biao Xie; Shui-Ming Zhang (Journal of Biosciences, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

Associative learning is necessary for airborne pheromones to activate sexual arousal-linked brain areas of female rats - Yao-Hua Zhang; Ming-Ming Tang; Xiao Guo; Xiao-Rong Gao; Jin-Hua Zhang; Jian-Xu Zhang (Behavioral Ecology and Sociobiology, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

p70S6K activation promotes the transdifferentiation of fibroblasts to myofibroblasts in pterygium tissue growth on the cornea - Xin-Rong Zhao; Ming-Chang Zhang; Hua-Tao Xie; Nan Ji; Le-Tian Sun (Biotechnology Letters, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Effects of potassium deficiency on root morphology, ultrastructure and antioxidant enzyme system in sweet potato (Ipomoea batatas [L.] Lam.) during early growth - Ming Liu; Ai-Jun Zhang; Xiao-Guang Chen; Rong Jin; Hong-Min Li; Zhong-Hou Tang (Acta Physiologiae Plantarum, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Comparison of immune responses to attenuated rabies virus and street virus in mouse brain - Fa-ming Miao; Shou-feng Zhang; Shu-chao Wang; Ye Liu; Fei Zhang; Rong-liang Hu (Archives of Virology, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Genetic Diversity and Population Structure Patterns in Chinese Cherry (Prunus pseudocerasus Lindl) Landraces - Tao Chen; Xiao-jiao Huang; Jing Zhang; Qing Chen; Yin Liu; Hao-ru Tang; Dong-ming Pan; Xiao-rong Wang (Plant Molecular Biology Reporter, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

The Inhibition Effect and Excessive Carbon Flux Resulting from Blocking Anthocyanin Biosynthesis Under Darkness in Begonia semperflorens - Kai Ming Zhang; Mei Li Guo; Dan He; Rong Hua Wu; Yong Hua Li (Journal of Plant Growth Regulation, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Calreticulin is localized at mitochondria of rat cardiomyocytes and affected by furazolidone - Hu Shan; Jin Wei; Ming Zhang; Lin Lin; Rui Yan; Yanhe Zhu; Rong Zhang (Molecular and Cellular Biochemistry, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Potential Effects of Mina53 on Tumor Growth in Human Pancreatic Cancer - Xiao-ping Tan; Wei-guo Dong; Qing Zhang; Zi-rong Yang; Xiao-fei Lei; Ming-hua Ai (Cell Biochemistry and Biophysics, 2014)

Attenuation of Reserpine-Induced Pain/Depression Dyad by Gentiopicroside Through Downregulation of GluN2B Receptors in the Amygdala of Mice - Shui-bing Liu; Rong Zhao; Xu-sheng Li; Hong-ju Guo; Zhen Tian; Nan Zhang; Guo-dong Gao; Ming-gao Zhao (NeuroMolecular Medicine, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Optimization of Extraction and Purification of Arctiin from Fructus arctii and Its Protection Against Glucose-Induced Rat Aortic Endothelial Cell Injury - Lai-chun Lu; Rong Zhang; Ming-bao Song; Shi-wen Zhou; Gui-sheng Qian (Cell Biochemistry and Biophysics, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Erratum to: Comparative Study of 1,064-nm Laser-Induced Skin Burn and Thermal Skin Burn - Yi-Ming Zhang; Jing Ruan; Rong Xiao; Qiong Zhang; Yue-Sheng Huang (Cell Biochemistry and Biophysics, 2014)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Comparative Study of 1,064-nm Laser-Induced Skin Burn and Thermal Skin Burn - Yi-Ming Zhang; Jing Ruan; Rong Xiao; Qiong Zhang; Yue-Sheng Huang (Cell Biochemistry and Biophysics, 2013)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

Halomonas nanhaiensis sp. nov., a halophilic bacterium isolated from a sediment sample from the South China Sea - Mei-Rong Long; Dao-Feng Zhang; Xin-Yi Yang; Xiao-Mei Zhang; Yong-Guang Zhang; Yuan-Ming Zhang; Honghui Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Oxidative Parameters in the Rat Brain of Chronic Mild Stress Model for Depression: Relation to Anhedonia-Like Responses - Chao Wang; He-ming Wu; Xiao-rong Jing; Qiang Meng; Bei Liu; Hua Zhang; Guo-dong Gao (The Journal of Membrane Biology, 2012)

Aldehyde dehydrogenase protein superfamily in maize - Mei-Liang Zhou; Qian Zhang; Ming Zhou; Lei-Peng Qi; Xiong-Bang Yang; Kai-Xuan Zhang; Jun-Feng Pang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Functional & Integrative Genomics, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

MicroRNA profiles and their control of male gametophyte development in rice - Hua Peng; Jun Chun; Tao-bo Ai; Yong-ao Tong; Rong Zhang; Ming-ming Zhao; Fang Chen; Sheng-hua Wang (Plant Molecular Biology, 2012)

Tryptophan decarboxylase plays an important role in ajmalicine biosynthesis in Rauvolfia verticillata - Wanhong Liu; Rong Chen; Min Chen; Haoxing Zhang; Meifang Peng; Chunxian Yang; Xingjia Ming; Xiaozhong Lan; Zhihua Liao (Planta, 2012)

Assay and characterization of an osmolarity inducible promoter newly isolated from Bacillus subtilis - Wei-Wei Zhang; Qiu-Rong Gao; Ming-Ming Yang; Hui Liu; Dun Wang (Molecular Biology Reports, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

[11C]DAC-PET for Noninvasively Monitoring Neuroinflammation and Immunosuppressive Therapy Efficacy in Rat Experimental Autoimmune Encephalomyelitis Model - Lin Xie; Tomoteru Yamasaki; Naotsugu Ichimaru; Joji Yui; Kazunori Kawamura; Katsushi Kumata; Akiko Hatori; Norio Nonomura; Ming-Rong Zhang; Xiao-Kang Li; Shiro Takahara (Journal of Neuroimmune Pharmacology, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

Single cysteine substitution in Bacillus thuringiensis Cry7Ba1 improves the crystal solubility and produces toxicity to Plutella xylostella larvae - Donghai Peng; Fenshan Wang; Nisha Li; Zhenyu Zhang; Rong Song; Zimin Zhu; Lifang Ruan; Ming Sun (Environmental Microbiology, 2011)
Summary Many Bacillus thuringiensis isolates have no demonstrated toxicity against insects. In this study, a novel holotype crystal protein gene cry7Ba1 was isolated from a ‘non‐insecticidal’ B. thuringiensis strain YBT‐978. The Cry7Ba1 protein showed high toxicity against Plutella xylostella larvae after the crystals were dissolved at pH 12.5, suggesting that the ‘non‐insecticidal’ properties of this protein were due to insolubility in the normal insect midgut pH environment. After the C‐terminal half of Cry7Ba1 was replaced by that of Cry1Ac or Cry1C proteins, the recombinant protein inclusions could be dissolved at pH 9.5, and exhibited high toxicity against P. xylostella larvae. This result proved the insolubility of Cry7Ba1 crystal was determined by the structure of its C‐terminal half. Further, six mutations were constructed by substituting cysteine residues with serine. Solubility studies showed that the crystals from mutants C697S, C834S and C854S could be dissolved at lower pH (10.5, 9.5 and 11.5 respectively). Bioassays showed that crystals from mutant C834S were toxic to P. xylostella larvae. Our discoveries suggest that a single cysteine residue located in the C‐terminal half of the protein determines the solubility and toxicity of some nontoxic crystal proteins. This study provides a strategy to isolate novel insecticidal crystal protein genes from ‘non‐insecticidal’ B. thuringiensis strains.

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

LPS pretreatment ameliorates multiple organ injuries and improves survival in a murine model of polymicrobial sepsis - Dong-Wei Shi; Jing Zhang; Hong-Ni Jiang; Chao-Yang Tong; Guo-Rong Gu; Yuan Ji; Hanssa Summah; Jie-Ming Qu (Inflammation Research, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

A new species of Zygophiala associated with the flyspeck complex on apple from China - Yongqiang Ma; Rong Zhang; Guangyu Sun; Haixia Zhu; Ming Tang; Jean C. Batzer; Mark L. Gleason (Mycological Progress, 2010)

Solid-state fermentation of cornmeal with the ascomycete Morchella esculenta for degrading starch and upgrading nutritional value - Gui-Ping Zhang; Feng Zhang; Wen-Ming Ru; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2010)

Detection of expression of influenza virus receptors in tissues of BALB/c mice by histochemistry - Zhang-Yong Ning; Min-Yi Luo; Wen-Bao Qi; Bo Yu; Pei-Rong Jiao; Ming Liao (Veterinary Research Communications, 2009)

Increased expression of Toll-like receptors 4 and 9 in human lung cancer - Yan-Bei Zhang; Feng-Lian He; Ming Fang; Tian-Feng Hua; Bi-Dan Hu; Zhi-Hong Zhang; Qi Cao; Rong-Yu Liu (Molecular Biology Reports, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Sorption of 1,1,1-trichloro-2,2-bis(p-chlorophenyl) ethane (DDT) by clays and organoclays - Rong-Ling Dai; Gang-Ya Zhang; Xiao-Zhi Gu; Ming Kuang Wang (Environmental Geochemistry and Health, 2008)

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies - Jian-Ming Chen; Chen Gao; Qi Shi; Bing Shan; Yan-Jun Lei; Chen-Fang Dong; Run An; Gui-Rong Wang; Bao-Yun Zhang; Jun Han; Xiao-Ping Dong (Archives of Virology, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Dependent mechanism of Chinese prepositions processing in the brain: evidence from event-related potentials - Huan-Hai Fang; Rong-Ping Zhang; Huan-Fei Fang; Ming-Yang Gao; Min Zheng; Xiao-Yu Sun (Neuroscience Bulletin, 2007)

BRD7 suppresses the growth of Nasopharyngeal Carcinoma cells (HNE1) through negatively regulating β-catenin and ERK pathways - Cong Peng; Hua Ying Liu; Ming Zhou; Li Ming Zhang; Xiao Ling Li; Shou Rong Shen; Gui Yuan Li (Molecular and Cellular Biochemistry, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Complex influence of rice variety, fertilization timing, and insecticide on population dynamics of Sogatella furcifera (Horvath) , Nilaparvata lugens (Stl) (Homoptera: Delphacidae) and their natural enemies in rice in Hangzhou, China - Zeng-Rong Zhu; Jiaan Cheng; Ming-Xing Jiang; Xiao-Xi Zhang (Journal of Pest Science, 2004)

Co-inheritance of specific genotypes of HSPG and ApoE gene increases risk of type 2 diabetic nephropathy - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

The heparan sulfate proteoglycan gene polymorphism: Association with type 2 diabetic nephropathy in Chinese - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Yanqing Wang; Huijuan Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)

GSTP1 polymorphisms and gastric cancer in a high-risk Chinese population - Veronica Wendy Setiawan; Zuo-Feng Zhang; Guo-Pei Yu; Qing-Yi Lu; Yong-Liang Li; Ming-Lan Lu; Ming-Rong Wang; Chun Hua Guo; Shun-Zhang Yu; Robert C Kurtz; Chung-Cheng Hsieh (Cancer Causes & Control, 2001)